Mesalamine-Mediated Amelioration of Experimental Colitis in Piglets Involves Gut Microbiota Modulation and Intestinal Immune Cell Infiltration - Huang, Yonggang; Wu, Miaomiao; Xiao, Hao; Liu, Hongnan; Yang, Guan (Frontiers in Immunology, 2022)
Mesalamine (MES), also known as 5-aminosalicylic acid, is effective in treating mild to moderate ulcerative colitis (UC). The mechanisms of its actions are not fully elucidated. The aim of this study was to investigate the effects of MES treatment on intestinal microbiota and immune system in dextran sulfate sodium (DSS)-induced UC model in post-weaning piglets. Eighteen weaned piglets were assigned randomly to the following treatments: control group (CON, distilled water); DSS group (DSS, 3% DSS); and MES group (MES, 3% DSS + 2 g/d MES). Our results showed that MES treatment alleviates DSS-induced colitis in piglets, as evidenced by reduced diarrhea index score and increased average daily gain. This is accompanied by decreased diamine oxidase activity, D-lactate level, and attenuated mucosal damage. MES treatment also decreased the abundance of Methanogens, reduced colon CD11b+ macrophage and CD3+ T cell infiltrations in piglets with DSS-induced colitis. Collectively, these data indicate that MES treatment-mediated colitis protection may involve microbiota and immune cell alterations.